1987
DOI: 10.1111/j.1365-2125.1987.tb03129.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to mental stress and physical provocations before and during long term treatment of hypertensive patients with beta‐adrenoceptor blockers or hydrochlorothiazide.

Abstract: 1 Cardiovascular and sympatho-adrenal responsiveness to mental stress (CWT; a colour word test), orthostatic testing (ORT) and a cold pressor test (CPT) were examined in three groups of hypertensive patients (n = 14-16) before and after 6 months treatment with metoprolol (243 ± 26 mg daily), propranolol (149 ± 16 mg daily) or hydrochlorothiazide (50 ± 8 mg daily) in an open trial design. 2 Treatment reduced outpatient blood pressures in the three groups similarly (from approximately 155/102 to 135/90 mm Hg). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
(69 reference statements)
2
11
0
Order By: Relevance
“…Bonelli et al [32] also found that propranolol did not affect the calculation stress-induced increase in E. On the other hand, mepindolol, which is similar to bopindolol, prevented the increase, in contrast to the present finding. The effect of 13-adrenoceptor blockers on the response to mental stress was also studied by Etiasson et al [36]. They found that the response of NE was increased by propranolol, but not by metoprolol, and that plasma E was decreased by metoprolol.…”
Section: Discussionmentioning
confidence: 95%
“…Bonelli et al [32] also found that propranolol did not affect the calculation stress-induced increase in E. On the other hand, mepindolol, which is similar to bopindolol, prevented the increase, in contrast to the present finding. The effect of 13-adrenoceptor blockers on the response to mental stress was also studied by Etiasson et al [36]. They found that the response of NE was increased by propranolol, but not by metoprolol, and that plasma E was decreased by metoprolol.…”
Section: Discussionmentioning
confidence: 95%
“…1986, 1987). While these studies did not examine MSNA responses, one reported that BP responsiveness was the same before and after 6 months of hydrochlorothiazide treatment (Eliasson et al.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies did not examine MSNA responses, one reported that BP responsiveness was the same before and after 6 months of hydrochlorothiazide treatment (Eliasson et al. 1987). Their subject population was dissimilar to ours; their subjects were younger (˜40-years old) and required a higher dose of HCTZ (50 mg) to control BP (Eliasson et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations